2015
DOI: 10.1021/acs.molpharmaceut.5b00208
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Antimicrobial Capture Coatings for Endotracheal Tubes: A Pharmaceutical Strategy Designed to Prevent Ventilator-Associated Pneumonia

Abstract: (2015). Hydrogel antimicrobial capture coatings for endotracheal tubes; a pharmaceutical strategy designed to prevent ventilator-associated pneumonia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…However, both of these additions have proven to be ineffective in preventing the spread of bacteria to the lower trachea and have the potential to damage the trachea (Inglis, Millar, Jones, & Robinson, 1989; Mietto et al, 2013). Additional prevention attempts have included various surface modifications to ETTs such as silver‐coated (Barnes et al, 2019; Olson, Harmon, & Kollef, 2002) and gentamicin‐containing hydrogel‐coated ETTs (Barnes et al, 2019; Jones, McCoy, Andrews, McCrory, & Gorman, 2015). Currently, silver‐coated ETTs are the only commercially approved antimicrobial ETTs in the United States.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both of these additions have proven to be ineffective in preventing the spread of bacteria to the lower trachea and have the potential to damage the trachea (Inglis, Millar, Jones, & Robinson, 1989; Mietto et al, 2013). Additional prevention attempts have included various surface modifications to ETTs such as silver‐coated (Barnes et al, 2019; Olson, Harmon, & Kollef, 2002) and gentamicin‐containing hydrogel‐coated ETTs (Barnes et al, 2019; Jones, McCoy, Andrews, McCrory, & Gorman, 2015). Currently, silver‐coated ETTs are the only commercially approved antimicrobial ETTs in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Additional prevention attempts have included various surface modifications to ETTs such as silver-coated (Barnes et al, 2019;Olson, Harmon, & Kollef, 2002) and gentamicin-containing hydrogel-coated ETTs (Barnes et al, 2019;Jones, McCoy, Andrews, McCrory, & Gorman, 2015). Currently, silver-coated ETTs are the only commercially approved antimicrobial ETTs in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…Concerning hydrophilic polymer materials, poly(2-hydroxyethyl methacrylate) (PHEMA) is one of the most widely used in the manufacture of medical devices, such as contact and intraocular lenses, and medical device coatings [26,27], because it exhibits blood and cell biocompatibility, low cytotoxicity, and thrombogenicity [28,29]. In addition, a variety of antimicrobial agents has been included into hydrogels and materials based on PHEMA to provide biocidal character as an additional property [26,30,31,32]. Herein, we prepared copolymers systems composed of 2-hydroxyethyl methacrylate (HEMA) and a methacrylic monomer bearing thiazolium moieties (MTARI) with the purpose of incorporating antimicrobial properties into PHEMA.…”
Section: Introductionmentioning
confidence: 99%
“…To conquer these limitations, a reasonable option is to use a sustained drug release technique to locally deliver anesthetic agent, which allows for an extended effective duration, a higher local drug concentration, and lower adverse effects. Recent studies showed that the sustained release of corticosteroids or antimicrobials from surface coatings, including electrospinning, hydrogel, and dip coatings, on endotracheal tubes (ETTs) is feasible and effective in reducing inflammatory reactions and preventing ventilator-related infection (16)(17)(18). Therefore, surface coating techniques may also be applicable to local LDC delivery for enhancing the local anesthetic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other reported ETT coating techniques, the evaporation of spray coating is faster, which reduces the impact on the substrate from dip coatings where the tube needs to be immersed in solvent (18), and can easily prepare a thin, uniform, and transparent coating. At the same time, hydrogel (17) and electrospinning (16) ETT coatings are thicker (0.17-0.2 mm), which may limit their application in small diameter ETTs, such as size 2.5: inner diameter =2.5 mm, and outer diameter =3.3 mm.…”
Section: Introductionmentioning
confidence: 99%